Stoic Ethics as a Guide to the Political Life in Marcus Aurelius - Bruno Alonso (Escritos, 2020)
Marcus Aurelius reigned from 161 A.D. to 180 A.D., and he ranks among the most successful emperors of the antonine dynasty. The success of his administration may be attributed to his philosopher personality and, more than that, to his stoic character. Meditations presents thoughts of a stoicism devotee, which reflects in moments of intimacy on the challenges that he faced throughout his life as an emperor. It is in the practice of the ethical precepts of stoicism that he finds his refuge. The text consists of a series of spiritual exercises which reaffirm the indifference to pleasures, contempt for fame, detachment from riches and abnegation for political power. This paper is a study of Meditations, and its main purpose is to elucidate how the stoic way of life is incorporated in the figure of the philosopher emperor; this, as a military function, as he was a commander of the Roman army in the war against the Nordics, where political virtue was tested. Amid the chaos of an insane struggle for the survival of Rome, he found in stoicism a precious source of inspiration. Marcus Aurelius was not dazzled by the cult of the emperor's personality; he acted for the natural right to freedom and guided his political actions for the common good. His stoic perseverance reveals itself in a harmonious conduct with the city, the rational and cosmic organism from which the emperor is a simple part.